Buckling behaviors and ultimate strengths of 6082-T6 aluminum alloy columns under eccentric compression – Part I: Experiments and finite element modeling. (October 2019) - Zhao, Yuanzheng; Zhai, Ximei; Wang, Jianhao
Abstract: Aluminum alloys, which function as load-bearing components or decorative materials, have been commonly applied to architectural structures. In this study, a combination of experiments and finite element analyses was conducted to investigate the stability behaviors and ultimate strengths of the 6082-T6 aluminum alloy columns subjected to eccentric compression. Prior to the loading tests, tensile coupon tests and measurement of the initial geometric imperfections for the columns were performed. The buckling behaviors of 30 pin-ended specimens, including 11 extruded square hollow section (SHS) columns and 19 extruded circular hollow section (CHS) columns, were investigated and the observed failure modes of the tested columns included overall buckling, local buckling and the coupling modes. Meanwhile, the ultimate strengths, deflections and surface strains in whole process under eccentric compression were recorded. The finite element (FE) models of the tested columns were developed using the non-linear finite element analysis (FEA) software ABAQUS, and the geometric and material nonlinearities were considered in the FE models. The validation of the FE models was performed against the test results; it was observed that the proposed FE models are sufficiently accurate to predict the ultimate strengths and buckling behaviors of the tested columns. Graphical abstract: Image 1 Highlights: A tensile coupon test of 6082-T6 aluminum alloy was carried out. A test of 30 eccentrically loaded aluminum alloy columns was performed. The FE models were developed using ABAQUS and validated against test results. Effect of the design parameters of FE models on simulated results was studied.